Improving Lecturer Performance Human Resource Development to Achieve the Vision and Mission of Faculty of Economics and Business: Case Study of Tangerang Raya University - Sundoro, Aries; Hariri, Hariri; Irwansyah, Novi; Juhaeni, Unes; Purnawan, Lesna (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the improvement of lecturers' performance, focusing on aspects of performance measurement and professionalism. The research uses a qualitative approach to depict the phenomena occurring in the field. Data collection techniques include triangulation through in-depth interviews with key informants, surveys, observation of actual events in the research field, and document studies, such as photographs, meeting notes, videos, and other social media content to supplement the actual data. The conclusion indicates that the performance of lecturers at the FEBI Faculty of Tangerang Raya University in Tangerang can be enhanced by recruiting qualified non-permanent lecturers with specialized skills in their fields. Other efforts include providing training and workshops for the FEBI lecturers, as well as implementing an E-Learning system to support the development of human resources aligned with the university's vision and mission.